Camera Sensor Network Localization Using FPGA - El-khatib, Lina Noaman; Hussin, Fawnizu Azmadi; Sebastian , Patrick (2010)
Camera networks are important in a video surveillance system. A lot of surveillance systems research has been done; most of it utilizes a general purpose computer. However, the latest trend is to use small, task specific and low power computer to process and control the system; in another word using embedded systems. This paper presents a camera network localization algorithm to be implemented on a FPGA device. An algorithm that uses object image tracking to determine cameras’ locations is used. For tracking moving objects, there are a lot of techniques available. Adaptive Hybrid Deference Algorithm is one of the tracking algorithms. We use that algorithm, simulate it and study its feasibility. A hardware design is needed before programming the FPGA. We have developed a hardware design model; which is currently under testing and simulation.